2018
DOI: 10.15252/emmm.201809962
|View full text |Cite
|
Sign up to set email alerts
|

Sea squirt alternative oxidase bypasses fatal mitochondrial heart disease

Abstract: Mitochondrial diseases are a diverse group of inborn disorders affecting cellular energy production by oxidative phosphorylation (OXPHOS) via the five (CI‐CV) mitochondrial respiratory chain (MRC) complexes. The sea squirt alternative oxidase (AOX) is able to bypass the distal part of the MRC and was shown to alleviate the consequences of CIII and CIV defects in several cellular and Drosophila models. In this issue of EMBO Molecular Medicine, Rajendran et al () demonstrate the first proof of concept in mammals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…So far two other animal models, both obtained due to heterologous expression of the tunicate C. intestinalis AOX in fruit ies and mice, have been used in research on AOX impact on animal physiology and the enzyme possible application in therapy of human mitochondrial diseases (e.g. [1,3,[9][10][11][12]. The data obtained for H. exemplaris could supplement the models due to the presence of native AOX as well as simplicity of the tardigrade culture and AOX research in intact specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far two other animal models, both obtained due to heterologous expression of the tunicate C. intestinalis AOX in fruit ies and mice, have been used in research on AOX impact on animal physiology and the enzyme possible application in therapy of human mitochondrial diseases (e.g. [1,3,[9][10][11][12]. The data obtained for H. exemplaris could supplement the models due to the presence of native AOX as well as simplicity of the tardigrade culture and AOX research in intact specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is suggested that AOX can bypass blockade or de ciency of the MRC complexes III and IV by restoring electron ow upstream of the MRC complex III. Consequently, AOX is considered to be an important element of a therapeutic strategy against impairment of these complexes [1,3,[9][10][11][12].…”
mentioning
confidence: 99%
“…A previous study [ 14 ] showed that niclosamide can damage the liver and gonad (liver-gonad), ganglion, and muscle tissues of O. hupensis , with systems such as those of the mitochondrion, endoplasmic reticulum, and nucleus being the most affected. The mitochondrion is an organelle central to the production of chemical energy; it is involved in carbohydrate, amino acid and fatty acid metabolism, redox homeostasis, and cell signal transduction pathways, and is responsible for more than 90% of the adenosine triphosphate (ATP) produced in the cells of animals [ 15 , 16 ]. Our previous studies on the enzymatic histochemistry and metabolic changes of O. hupensis in response to niclosamide revealed that the activities of cytochrome c oxidase (CCO), succinic dehydrogenase (SDH), and glucose-6-phosphatase in the respiratory chain of mitochondrial oxidative phosphorylation decreased after niclosamide treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is suggested that AOX can bypass blockade or deficiency of the MRC complexes III and IV by restoring electron flow upstream of the MRC complex III. Consequently, AOX is considered to be an important element of a therapeutic strategy against impairment of these complexes [1,3,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%